AB0538 PREGNANCY OUTCOMES IN PATIENTS WITH TAKAYASU'S ARTERITIS: CASE SERIES. (2nd June 2020) - Vanegas, A.; Torres, F.; Muñoz, C.; Jaramillo, D.; Hernandez, L.; Vásquez, G.; Restrepo Escobar, M.; González, L. A.; Velásquez, I.
Abstract : Background: Takayasu's arteritis (TA) is most prevalent in women of childbearing age. Although its activity and risk of relapse are low during pregnancy, up to 40% of patients may have unfavorable obstetric outcomes and therefore it is important to know their clinical behavior. Objectives: To describe the clinical features and obstetric outcomes of pregnant women with TA treated in a tertiary center. Methods: Retrospective evaluation of medical records of 6 pregnancies in 6 women with TAs treated in a tertiary center in Medellin, Colombia between 2011-2018. Results: Six women who were 17.5 (RI 9.25) years old at diagnosis and 24 (RI 8.25) years old at delivery, their disease duration were 5.5 (RI 10.5) years. Three patients had extensive aortic involvement classified as Numano type V, two as type IIB and one as type I. At delivery, three patients were active and required immunosuppressants, five had high blood pressure, one developed preeclampsia in the second trimester, one had severe mitral and tricuspid insufficiency with decreased ejection fraction of the left ventricle; two had aneurysms (left subclavian artery and ascending aorta). There were two fetal deaths, one due to intrauterine growth restriction and placental insufficiency and another of unknown etiology; both patients with disease activity, extensive aortic condition and arterial hypertension; no pregnancy resulted in abortion or preterm birth. Five deliveries were by caesarean section by maternal indication; there was no aortic dissection, aneurismal rupture or cerebral hemorrhage (table). Conclusion: Pregnant women with active disease and extensive aortic condition presented unfavorable obstetric results, suggesting that an inadequate control of vasculitis may lead to greater maternal-fetal complications. References: [1]Assad APL, da Silva TF, Bonfa E, Pereira RMR. Maternal and Neonatal Outcomes in 89 Patients with Takayasu Arteritis (TA): Comparison Before and After the TA Diagnosis. J Rheumatol. 2015 Oct;42(10):1861–4. [2]Hidaka N, Yamanaka Y, Fujita Y, Fukushima K, Wake N. Clinical manifestations of pregnancy in patients with Takayasu arteritis: experience from a single tertiary center. Arch Gynecol Obstet. 2012 Feb;285(2):377–85. Disclosure of Interests: None declared